Spending Experiences among K-Pop Fans in Indonesia: A Cross-Sectional Study of Financial Prioritisation, Budget Reallocation, Coping, and Emotional Investment - Kurnia Khafidhatur Rafiah; Irsyad Kamal; Chiara Zivka Manayra (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines spending experiences among K-Pop fans in Indonesia by distinguishing financial prioritisation, budget reallocation, coping-oriented spending, and emotional investment, while exploring their associations with selected respondent characteristics. An exploratory cross-sectional online survey was conducted among 164 K-Pop fans who had prior experience using a paid K-Pop artist-frame self-photo booth service. Four five-point Likert items were analysed separately, supported by descriptive statistics and Spearman rank-order correlations, with 16 primary correlations adjusted using the Holm procedure. Agreement was lowest for financial prioritisation during financial difficulty (8.5%) and higher for budget reallocation (32.9%), coping-oriented spending (60.4%), and emotional investment (50.0%). The perceived role of idols in consumption decisions was positively associated with financial prioritisation (ρ=.278), coping-oriented spending (ρ=.278), and emotional investment (ρ=.344), while monthly K-Pop spending was associated with financial prioritisation (ρ=.233) and emotional investment (ρ=.298). Income or allowance and fandom duration showed no significant associations after adjustment. The four spending experiences were positively interrelated, with correlations ranging from ρ=.397 to ρ=.577, yet remained conceptually distinct. These findings suggest that fandom-related expenditure should be understood through differentiated financial and affective dimensions rather than as a uniform form of excessive consumption. The study provides an empirical basis for examining how emotional meanings and financial practices intersect within contemporary K-Pop consumer culture.